Program Pengintegrasian Teknologi dalam Pembelajaran untuk Guru SD/MI Kecamatan Karangploso Kabupaten Malang - Ahdhianto, Erif; Masula, Siti; Thohir, M. Anas (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this technology integration program in learners is to learn about how to make interesting learning videos and apply e-learning. It is hoped that in this community service activity, teachers can master interactive and interesting learning media in the form of learning videos and apply them to e-learning. The implementation of this community service activity is in the form of presentations regarding the introduction of learning media, OBS software, e-learning, and how to make learning videos. The method used is the preparation of materials and software, implementation methods related to how to operate OBS software, and e-learning and practical methods are carried out in the form of making interactive learning video media according to the material taught by the teacher. The evaluation was carried out in this training by observing the differences in the skills of teachers in making learning videos after the implementation of the training. Based on the results that have been achieved. The evaluation of the results training was assessed from the participation and practical assignments of making interactive videos according to the material taught by the teacher. Then the results of making interactive learning videos are implemented in the schools of each SD/MI teacher.